Efeitos da luminosidade no crescimento de mudas de Caesalpinia ferrea Mart. ex Tul. (Leguminosae, Caesalpinoideae) - Lima, Juliana Domingues [UNESP]; Silva, Breno Marques Da Silva [UNESP]; Moraes, Wilson Da Silva; Dantas, Vânia Andréa Valente; Almeida, Cilene Chaves (My University, 2008)
Caesalpinia ferrea is a species used a lot as a medicinal plant, for urban arborization and landscape design in the state of Amapa. Yet there is not much ecophysiological information available on it. Light is an important environment factor that controls processes associates with the accumulation of dry matter, contributing thus for plant growth. The object of this research was to study the effect of different luminosity levels on the growth of seedlings of this species. The seedlings were transplanted to plastics bags containing a mixture of soil and sand (2:1), which were maintained in the full sun, under artificial shade with reduction of 50% and 70% of the luminosity and under natural shade of a closed canopy of forest. The experimental design was completely randomized with five replicates. Seedlings submitted to natural shade showed strong growth inhibition. In the full sun, the seedlings presented higher net assimilatory rate (NAR), lower shoot/root ratio (SRR) and lower leaf area ratio (LAR). The results showed little difference in the growth and biomass allocation between seedlings kept in 50 and 70% shade; the seedlings submitted to this treatment presented higher values of SRR and LAR. This indicates plasticity which influences a possible increase in light capture and is important, therefore, to keep the seedling growth and survival under low light levels. The results as a whole showed morphological and physiological adjustment to different light levels in Caesalpinia ferrea.
Effects of luminosity on the growth seedlings of Caesalpinia ferrea Mart. ex Tul. (Leguminosae, Caesalpinoideae)
Keywords: Initial growth; Light requirements; Shading; Tropical trees; Caesalpinia; Caesalpinia ferrea; Fabaceae